An in vivo 11C‐PK PET study of microglia activation in Fatal Familial Insomnia. Issue 1 (9th December 2017) - Iaccarino, Leonardo; Presotto, Luca; Bettinardi, Valentino; Gianolli, Luigi; Roiter, Ignazio; Capellari, Sabina; Parchi, Piero; Cortelli, Pietro; Perani, Daniela
Abstract: Objective: Postmortem studies reported significant microglia activation in association with neuronal apoptosis in Fatal Familial Insomnia (FFI), indicating a specific glial response, but negative evidence also exists. An in vivo study of local immune responses over FFI natural course may contribute to the understanding of the underlying pathogenesis. Methods: We included eight presymptomatic subjects (mean ± SD age:44.13 ± 3.83 years) carrying the pathogenic D178N‐129 met FFI mutation, one symptomatic patient (male, 45 yrs. old), and nine healthy controls (HC) (mean ± SD age: 44.00 ± 11.10 years.) for comparisons. 11 C‐(R)‐PK11195 PET allowed the measurement of Translocator Protein (TSPO) overexpression, indexing microglia activation. A clustering algorithm was adopted to define subject‐specific reference regions. Voxel‐wise statistical analyses were performed on 11 C‐(R)‐PK11195 binding potential (BP) images both at the group and individual level. Results: The D178N‐129 met/val FFI patient showed significant 11 C‐(R)‐PK11195 BP increases in the midbrain, cerebellum, anterior thalamus, anterior cingulate cortex, orbitofrontal cortex, and anterior insula, bilaterally. Similar TSPO increases, but limited to limbic structures, were observed in four out of eight presymptomatic carriers. The only carrier with the codon 129 met/val polymorphism was the only one showing an additional TSPO increase in the anterior thalamus. Interpretation: In comparison to nonprion neurodegenerative diseases, the observed lack of a diffuse brain TSPO overexpression in preclinical and the clinical FFI cases suggests the presence of a different microglia response. The involvement of limbic structures might indicate a role for microglia activation in these key pathologic regions, known to show the most significant neuronal loss and functional deafferentation in FFI.